Characterisation of the borgwaldt LM4E system for in vitro exposures to undiluted aerosols from next generation tobacco and nicotine products (NGPs). (March 2018) - Adamson, Jason; Jaunky, Tomasz; Thorne, David; Gaça, Marianna D.
Abstract: Traditional in vitro exposure to combustible tobacco products utilise exposure systems that include the use of smoking machines to generate, dilute and deliver smoke to in vitro cell cultures. With reported lower emissions from next generation tobacco and nicotine products (NGPs), including e-cigarettes and tobacco heating products (THPs), diluting the aerosol is potentially not required. Herein we present a simplified exposure scenario to undiluted NGP aerosols, using a new puffing system called the LM4E. Nicotine delivery from an e-cigarette was used as a dosimetry marker, and was measured at source across 4 LM4E ports and in the exposure chamber. Cell viability studies, using Neutral Red Uptake (NRU) assay, were performed using H292 human lung epithelial cells, testing undiluted aerosols from an e-cigarette and a THP. E-cigarette mean nicotine generated at source was measured at 0.084 ± 0.005 mg/puff with no significant differences in delivery across the 4 different ports, p = 0.268 (n = 10/port). Mean nicotine delivery from the e-cigarette to the in vitro exposure chamber (measured up to 100 puffs) was 0.046 ± 0.006 mg/puff, p = 0.061. Aerosol penetration within the LM4E was 55% from source to chamber. H292 cells were exposed to undiluted e-cigarette aerosol for 2 h (240 puffs) or undiluted THP aerosol for 1 h (120 puffs). There were positive correlations between puff number and nicotine in the exposed culture media, R 2  = 0.764 for the e-cigarette and R 2  = 0.970 for the THP. NRU determined cell viability for e-cigarettes after 2 h' exposure resulted in 21.5 ± 17.0% cell survival, however for the THP, full cytotoxicity was reached after 1-h exposure. Graphical abstract: Highlights: The LM4E analytical vaping machine was assessed for NGP aerosol exposure in vitro . Lung epithelial cells were exposed to undiluted e-cigarette or THP aerosol and assessed with NRU. Dosimetry was confirmed by a linear correlation of nicotine in the exposed culture media with increasing puff number. Full cytotoxicity was achieved in 1 h with the THP; cell survival was 22% after 2 h' exposure to e-cigarette aerosol. Biological responses showed parity when diluted and undiluted aerosol exposures were aligned with exposed nicotine.